En jordgrav fra tidlig-neolitisk tid - Stürup, Bjørn (Kuml, 1965)
A New Earth-Grave from the Early Neolithic Period ’Konens Høj’ is the name of a natural sandbank which juts out in the flat meadowland west of Stubbe Lake in southern Djursland. The meadows were in Atlantic times part of a fjord, of which Stubbe Lake is the only remnant. In 1962, an exploratory trench revealed a Stone Age settlement layer here, and in 1963-1965 Kulturhistorisk Museum, Randers, uncovered an area of 350 sq.m in and around the settlement layer, collecting large quantities of potsherds and flint of the Early Neolithic, which still await study. The result of a C14-dating of a sample from a charcoal layer on the site is, however, available. This analysis (National Museum C14 Laboratory, K-923) yields a date 3310 ± 100 B.C. This is thus the earliest dated Neolithic settlement in Denmark. In the course of the investigation, a grave was uncovered (fig. 1) lying in a planed area which had been excavated in the settlement layer down to virgin soil. The floor of the grave was an almost horizontal, rectangular paving of limestone cobbles of varying size on virgin sand, measuring 3.50 m X 0.80 m and lying slightly off E-W. On each side of the paving, two parallel rows of stones had been laid with varying regularity, and at each end of the paving a pile of stones was found. At the east end of the grave a depression could be seen, and when the paving was removed, an oval pit was revealed under this depression and at the west end of the grave. The pits were situated with their long axes across the grave, this length corresponding to the width of the grave floor. The east pit extended about 1.20 m under the grave floor, while the west pit had a depth of only about 1 m (fig. 2 a-b). In each case flat stones had been wedged down from both sides, and a clear displacement away from the grave could be observed at the bottom of the pit. These pits can only be understood as foundations for vertical wooden gables which closed the inner grave at both ends, and it seems reasonable to suppose a horizontal ridge-piece between the gables. It seems likely that the two parallel rows of stones on each side of the paving have served as supports for a roof resting on the inner row and held in position by the outer. No direct traces of such a roof were found in the clean sand between the rows, but this may only mean that the roof was not very high. In the sand covering the paving, there were occasional charcoal fragments with a more concentrated occurrence of larger pieces on the south side. A C14-analysis of this (N.M. C14 Laboratory, K-919) gave a date 2900 ± 100 B.C. The annual rings of these pieces of oak were so irregular and twisted that they probably stem from branches and not large pieces of timber, so there can be little difference in age between the burnt wood and the grave. A suggested reconstruction is shown in figs. 3-4, taking account of the following main features: 1) The grave has been constructed with a paved floor and a wooden superstructure. 2) The latter has been carried on two gables of massive timber, between which there has been some kind of ridge-piece. 3) The roof has been of branches sloping down to ground level, where they have been held in position by two rows of stones on each side of the grave. 4) The gables have at some stage been pressed in towards the middle of the grave as a result of the roof having burnt. Grave fumiture: At the west end of the grave, some tooth enamel and poorly preserved bone fragments (fig. 5) lay directly on the paving. Under the largest piece of bone -a lower arm fragment a piece of copper plate (fig. 6) was found. This is irregular in shape and no original edges seem to have been preserved. Length 59 mm, width 26 mm, thickness 0.8 mm. There is a slight corrugation along the length (5812 a). About 25 cm south of the bone fragments, a spiral ring of copper, presumably a finger ring, was found (fig. 7). The preserved piece comprises only about 3/4 turn of a spiral, but at excavation nearly 1½ turns could be seen. The spiral is made of copper ribbon about 0.3 mm thick and 10 mm wide, with the long edges folded in to meet in the middle, on the inside of the ring. Overall length 27 mm, greatest width 5 mm, greatest internal diameter 11 mm (5812 b). About the middle of the grave, towards the south, a large hour-glass shaped piece of amber occurred (fig. 8) which from its shape and position in the grave should perhaps be interpreted as a belt fastening. Roughly in the middle is a groove which seems to be slightly worn, perhaps from a suspension string. Length 70 mm, greatest thickness 35 mm, smallest thickness in the groove 25 mm. The piece is a rounded, irregular clump (5812 c). At the foot of the grave, the east end, a pot was found which had partly slipped into the depression above the foundation pit mentioned above (fig. 9-10). It clearly refers the grave to the Beaker Culture C complex, as classified by C. J. Becker (1). This lug vessel is 20 cm high, the neck comprising 12 cm; the greatest diameter above the body is 14.5 cm and the rim diameter 7.4 cm. The base is without a standing surface. From the neck to the shoulder there are four small band-shaped Jugs, placed in pairs. The neck is nearly cylindrical, the rim slightly turned but not thickened. On the shoulder the vessel is decorated with four groups of vertical grooves. The body is dirty yellow with a coarse temper of sharp crushed granite and the surface is smooth and greyish brown to dirty yellow in colour. Firing is fairly good, but both body and base were poorly preserved (5812 d). Finally, mention must be made of a piece of amber (fig. 8), found at the east end between the hour-glass shaped piece of amber and the pot. The fragmented piece has originally been almost rectangular with rounded corners. One side is almost flat, the other slightly convex. Near the middle, there is a somewhat irregular, roughly cylindrical perforation with slight traces of wear. Near one end there is a small pit, as for an unfinished perforation from the convex side. Length 60 mm, width 42 mm, thickness 14 mm (5812 e). In spite of the paucity of preserved skeletal material, the position of the skeleton can be reasonably ascertained -lying on the right side with the face turned south. One hand has lain in front of the face (copper ring), the other either above or below the neck (bone fragment over the copper plate). Assuming the hour-glass shaped piece of amber is a belt fastening, the corpse has been buried clothed. None of the preserved bone fragments is burnt, so assuming the burning of the grave roof did in fact occur, the fire must have been relatively slight or the dead must have been covered with a layer of sand before the fire (very thin, because the charcoal just above the floor stems from the burnt roof). Nothing suggests that the grave has ever been covered by a tumulus and only in connection with the piles of stones at the gable ends and in the foundation pits was there any settlement material (potsherds and shells) -above the grave itself there was only clean sand. Whether this was due to deliberate infilling or sand drift could not be ascertained. Here we have one more of the relatively rare earth graves from the Early Neolithic. The two imported copper objects and the lug vessel give a clear cultural reference to earlier finds from this period -the pot, for instance, has a near parallel in finds from the nearby Barkær settlement. The C14-dating may seem surprisingly early, but a corresponding dating applies to an English grave of identical construction, Wayland’s Smithy, 2820 ± 130 B.C. The latter, however, differs in being a communal grave for at least 14 persons without grave furniture and in having been covered by a small long barrow. Bjørn Stürup.